Perencanaan Strategis SI/TI Menggunakan Metodologi Ward And Peppard (Studi Kasus : Gallery Group) - Indra Kristiawan; Augie David Manuputty (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Gallery Group is a company that has several branch stores that sell various types of cellphones and accessories. The operational activities of this store already use IS/IT, but in use it is still not optimal because many business processes in this company have not implemented the use of IS/IT. Because of this, in the end there are many errors caused by human factors in every existing business process. Therefore, it takes the right IS/IT strategic planning for the company. This study uses the Ward and Peppard methodolgy which consists of several analyzes, namely SWOT, Porter's Five Forces, and McFarlan Strategic Grid. This research will produce outputs, namely recommendations that are useful for the company from the results of the analysis of the internal and external environment of IS/IT in the company. The IS/IT proposal will be mapped using McFarlan Strategic Grid analysis and can be implemented within the next two years.